2011
DOI: 10.1021/np2004193
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxylonols C–F, Benzo[j]fluoranthenes from Hypoxylon truncatum

Abstract: Four novel benzo[j]fluoranthene derivatives, hypoxylonols C (3), D (4), E (5), and F (6), have been isolated from the mushroom Hypoxylon truncatum, together with two known benzo[j]fluoranthene derivatives, hypoxylonols A (1) and B (2). The structures were established by analysis of NMR spectroscopic data and X-ray diffraction data. Compounds 4 and 5 showed antiproliferative activity against HUVECs (human umbilical vein endothelial cells) and HUAECs (human umbilical artery endothelial cells).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 10 publications
(14 reference statements)
2
33
0
1
Order By: Relevance
“…Although both 1 and 3 had (6bR) absolute conguration, the geometry of their annulations is different as reected by the opposite signs of the corresponding CEs. The (6bR) absolute conguration of 3 compares well with the reported absolute conguration of hypoxylonol C (5), 27 which may also suggest (1S) absolute conguration for 3.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Although both 1 and 3 had (6bR) absolute conguration, the geometry of their annulations is different as reected by the opposite signs of the corresponding CEs. The (6bR) absolute conguration of 3 compares well with the reported absolute conguration of hypoxylonol C (5), 27 which may also suggest (1S) absolute conguration for 3.…”
Section: Resultssupporting
confidence: 77%
“…The known compounds were identied as daldinone C (4), 28 hypoxylonol C (5), 27 daldinone B (6), 29 3,4-dihydro-3,4,6,8trihydroxy-l(2H)-naphthalenone (7), 30,31 (R)-scytalone (8), 31,32 and 1-hydroxy-8-methoxynaphthalene (9) 33 based on their NMR and MS spectroscopic data and by comparison with the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Specific inhibition of the MAPK superfamily, which is involved in directing cellular responses, reduces caspase-mediated apoptosis [ 2 , 9 ]. Recent studies have shown that inhibition of JNK, ERK, and p38 blocked caspase-3-mediated apoptosis in cisplatin-induced proximal tubular damage, although this mechanism remains unclear [ 4 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, interest in the production of secondary metabolites from mushrooms has increased due to their various biological activities [ 10 , 11 ]. Among these, Hypoxylon truncatum (family Xylariaceae), an inedible ball-shaped wood-rotting fungus, was reported to contain unique benzo[ j ]fluoranthene compounds [ 12 , 13 , 14 , 15 , 16 ]. During our search for new bioactive secondary metabolites of Korean wild mushrooms, we collected the H. truncatum mushroom (Gangneung city, Korea) and isolated three major compounds from it: hypoxylonol C ( 1 ), hypoxylonol F ( 2 ), and 4,5,4′,5′-tetrahydroxy-1:1′-binaphthyl (BNT) ( 3 ), from a crude methanol extract.…”
Section: Introductionmentioning
confidence: 99%
“…Tabela 18 -Dados de RMN 1 H (600 MHz) e 13 C (150 MHz) da amostra 21D5A(54).Deslocamentos químicos em δ (ppm) obtidos em acetona-d6Tabela 19 -Dados de RMN 1 H (600 MHz) e 13 C (150 MHz) da amostra 21D5C(55).Deslocamentos químicos em δ (ppm) obtidos em acetona-d6Tabela 20 -Dados de RMN 1 H (600 MHz) e 13 C (150 MHz) da amostra 21D5E(56).Deslocamentos químicos em δ (ppm) obtidos em acetona-d6Tabela 21 -Dados de RMN 1 H (600 MHz) e 13 C (150 MHz) da amostra HM11-32E (57) 89. O estudo químico do meio de cultura produzido pelo fundo da linhagemRoussoella sp.…”
unclassified